Assessment for familial pattern and association of polymorphisms in KIAA0319 gene with specific reading disorder in children from North India visiting a tertiary care centre: A case–control study. (8th December 2019) - Sharma, Pawan; Sagar, Rajesh; Deep, Raman; Mehta, Manju; Subbiah, Vivekanandhan
Abstract : Genetic association studies have identified KIAA0319 gene as a possible susceptibility locus for reading disorder; however, very few studies are available from India. The study was planned to investigate the familial pattern and association of KIAA0319 polymorphisms among children with reading disorder visiting a tertiary centre in North India. This is a case–control, familial, and genetic association study on 30 children diagnosed with reading disorder (ICD‐10) and 30 matched healthy controls and their families. The Aggregate Neurobehavioral Student Health and Educational Review System was administered on parents of probands and controls for reading problems in their siblings, and Adult Reading Questionnaire was administered for parents of both groups. The blood sample was taken from probands, and DNA was isolated. Four KIAA0319 coding sequence single nucleotide polymorphisms (SNPs; rs4504469, rs6935076, rs2038137, and rs2179515) were genotyped using SNaPshot single nucleotide extension. The incidence of reading problem was significantly higher in families of probands as compared with families of controls. There were no significant differences in both groups regarding the frequency of alleles of four SNPs. The reading disorder showed a significant familial pattern, but KIAA0319 gene did not appear to be a susceptibility factor. Future replications with larger samples and whole genome studies are warranted.